Recent advances in biopolymer-based hemostatic materials. (21st September 2022) - Mecwan, Marvin; Li, Jinghang; Falcone, Natashya; Ermis, Menekse; Torres, Emily; Morales, Ramon; Hassani, Alireza; Haghniaz, Reihaneh; Mandal, Kalpana; Sharma, Saurabh; Maity, Surjendu; Zehtabi, Fatemeh; et al.
Abstract: Hemorrhage is the leading cause of trauma-related deaths, in hospital and prehospital settings. Hemostasis is a complex mechanism that involves a cascade of clotting factors and proteins that result in the formation of a strong clot. In certain surgical and emergency situations, hemostatic agents are needed to achieve faster blood coagulation to prevent the patient from experiencing a severe hemorrhagic shock. Therefore, it is critical to consider appropriate materials and designs for hemostatic agents. Many materials have been fabricated as hemostatic agents, including synthetic and naturally derived polymers. Compared to synthetic polymers, natural polymers or biopolymers, which include polysaccharides and polypeptides, have greater biocompatibility, biodegradability and processibility. Thus, in this review, we focus on biopolymer-based hemostatic agents of different forms, such as powder, particles, sponges and hydrogels. Finally, we discuss biopolymer-based hemostatic materials currently in clinical trials and offer insight into next-generation hemostats for clinical translation. Graphical Abstract: